Stock Trading Classifier with Multichannel Convolutional Neural Network - Nascimento, Davi; Costa, Anna; Bianchi, Reinaldo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2020)
Stock market forecasting has been a quite popular challenge in machine learning research. Recently, studies have been using deep learning techniques, such as Convolutional Neural Networks (CNN), to perform regression on the prices or classification on trading signal as an operation indication. However, they did not reach a satisfactory financial result. In this work we aim to design a financially profitable stock market method by proposing a novel approach called Multichannel CNN Trading Classifier (MCNN-TC). The model was evaluated using data from the Brazilian stock market. The results indicate a satisfactory financial trading performance compared to the Buy and Hold strategy and good classification metrics.